2017
DOI: 10.1177/2168479017696260
|View full text |Cite
|
Sign up to set email alerts
|

The Benefit-Risk Assessment of Medicines: Experience of a Consortium of Medium-Sized Regulatory Authorities

Abstract: Overall, the authorities believed that the project had given them a better understanding of the value of using a structured approach to the benefit-risk assessment of medicines as well as enabling shared learnings between the authorities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…The revised International Council for Harmonisation (ICH)'s M4E guidance (revision 2), which was approved in 2015, may have played a facilitating role in this regard, although no respondent specifically referenced it [4]. The M4E revision set forth a standard format for presenting a product's benefit-risk assessment, one that incorporated the key elements found in the FDA's Benefit-Risk Assessment Grid [5]. Thus, companies are required to use this structured format when submitting marketing authorization applications via the electronic Common Technical Document (eCTD).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The revised International Council for Harmonisation (ICH)'s M4E guidance (revision 2), which was approved in 2015, may have played a facilitating role in this regard, although no respondent specifically referenced it [4]. The M4E revision set forth a standard format for presenting a product's benefit-risk assessment, one that incorporated the key elements found in the FDA's Benefit-Risk Assessment Grid [5]. Thus, companies are required to use this structured format when submitting marketing authorization applications via the electronic Common Technical Document (eCTD).…”
Section: Discussionmentioning
confidence: 99%
“…The comparatively limited use of qBRA within a company's portfolio of products, however, is consistent with recommended practice in this area. qBRA methods are most appropriate for complex decision-making, especially when the tradeoffs between benefits and risks are highly preference sensitive [5]. Results, however, suggest that qBRA may be underutilized to some extent, due to a variety of factors-perceived uncertainty regarding the value proposition, lack of consensus regarding which qBRA methods to use in which circumstances and how to implement them internally, and the absence of regulatory guidance in this area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of the UMBRA (Universal Methodology for Benefit-Risk Assessment) framework makes steps towards this structured regulatory decision-making process as it incorporates several frameworks (PrOACT-URL, PhRMA BRAT and FDA 5-step framework) [ 131 ]. The UMBRA framework uses benefit-risk summary template and corresponding user manual to clearly communicate benefit risk analysis to all stakeholders and upon review was found to be of value by several regulatory agencies [ 132 , 133 ].…”
Section: The Biorima Risk Management Frameworkmentioning
confidence: 99%